Modul celik huruf dalam kata nama am dan kata nama khas dalam kalangan murid SJK(T) Kajang dan SJK(T) Batu Caves - Subramaniam, Vijayaletchumy; Nagasundram, Usha (UKM, 2024)
Errors in capital and lowercase letter usage impede the formation of coherent sentences in Malay. In order to address this problem, the Design and Development Research (DDR) method first presented by Richey and Klein (2007) was applied in the development of the Lowercase and Uppercase Literacy Module in Common Nouns and Special Nouns. The modules are arranged by Reigeluth and Stein’s (1983) Elaboration Theory. This research aims to assess how the Letter Literacy Module in Common Nouns and Proper Nouns affects non-native speakers of Malay’s language proficiency. The participants in the study were 120 fifth-grade students from SJK(T) Kajang and SJK(T) Batu Caves who were SJK(T) Tamil National Type School students. Both a pre-test and post-test are used to assess the module’s effectiveness. After considering the percentage and frequency of the scores, student evaluation results are statistically descriptively analysed. The study analysis’s findings indicate that after using the module, students’ post-test achievement percentage increased. The findings of the study demonstrate that the Letter Literacy Module in Common Nouns and Proper Nouns can help teachers teach and learn the Malay language, particularly in the writing domain, by helping students comprehend the proper use of letters in writing.